2020
DOI: 10.1111/roie.12484
|View full text |Cite
|
Sign up to set email alerts
|

Production networks in Europe: A natural experiment of the European Union enlargement to the east

Abstract: Proximity plays an important role for trade relations, in particular, when the products traded are intermediates that are used in several stages of the production process. In addition, the size of the market and relative factor endowments or economic behavior are equally influential

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Nauro F. Campos et al [12] tested the positive economic effects of integration on member countries using synthetic control methods in both positive and negative. Martíne-Zarzoso et al focused on the 2004 enlargement of the European Union to the East and treats it as a natural experiment, who found that the effect of the 2004 EU enlargement has been positive for both intermediate and final goods trades, and it is, in general, greater for final goods [19]. Burghof and Gehrung showed that the European single financial market positively influenced economic growth across a variety of subsamples of EU member states using a difference-indifference design [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nauro F. Campos et al [12] tested the positive economic effects of integration on member countries using synthetic control methods in both positive and negative. Martíne-Zarzoso et al focused on the 2004 enlargement of the European Union to the East and treats it as a natural experiment, who found that the effect of the 2004 EU enlargement has been positive for both intermediate and final goods trades, and it is, in general, greater for final goods [19]. Burghof and Gehrung showed that the European single financial market positively influenced economic growth across a variety of subsamples of EU member states using a difference-indifference design [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bohle & Greskovits, 2012;Bruszt & Vukov, 2018;Podkaminer, 2013;Sapir, 2011;Shields, 2014), which has been viewed as a natural experiment (e.g. Hornok, 2010;Martínez-Zarzoso et al, 2020) for testing theories of market integration and trade (e.g. Balassa, 1961Balassa, , 1963Krugman, 1991;Krugman & Venables, 1990).…”
Section: Cluster Analyses Based On Gross Sectorial Exports and Coeffi...mentioning
confidence: 99%
“…This second case study addresses the Central-Eastern enlargement of the European Union [33,[61][62][63][64], which has been viewed as a natural experiment [65,66] for testing theories of market PLOS ONE integration and trade [67][68][69][70]. Specifically, this case study tracks the production-structural trajectories of the set of 'Eastern' countries that joined the EU in 2004 -the so-called 'A8' countries consisting of Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Slovakia, and Slovenia-and also Bulgaria and Romania, both joining three years later.…”
Section: Case Study: Regional Structural Transformations During the E...mentioning
confidence: 99%